Rotenone-induced PINK1/Parkin-mediated mitophagy: establishing a silkworm model for Parkinson’s disease potential - Zhang, Hantao; Yang, Jinyue; Guo, Yinglu; Lü, Peng; Gong, Xun; Chen, Keping; Li, Xiubin; Tang, Min (Frontiers in Molecular Neuroscience, 2024)
Parkinson's disease (PD), ranking as the second most prevalent neurodegenerative disorder globally, presents a pressing need for innovative animal models to deepen our understanding of its pathophysiology and explore potential therapeutic interventions.The development of such animal models plays a pivotal role in unraveling the complexities of PD and investigating promising treatment avenues. In this study, we employed transcriptome sequencing on BmN cells treated with 1 µg/mL rotenone, aiming to elucidate the underlying toxicological mechanisms. The investigation brought to light a significant reduction in mitochondrial membrane potential induced by rotenone, subsequently triggering mitophagy. Notably, the PTEN induced putative kinase 1 (PINK1)/Parkin pathway emerged as a key player in the cascade leading to rotenone-induced mitophagy. Furthermore, our exploration extended to silkworms exposed to 0.05 mg/mL rotenone, revealing distinctive motor dysfunction as well as inhibition of TH gene expression. These observed effects not only contribute valuable insights into the impact and intricate mechanisms of rotenone exposure on mitophagy but also provide robust scientific evidence supporting the utilization of rotenone in establishing a PD model in the silkworm. This comprehensive investigation not only enriches our understanding of the toxicological pathways triggered by rotenone but also highlights the potential of silkworms as a valuable model organism for PD research.